"Modern Band" as school music: A case study. (May 2018) - Byo, James L.
This purpose of this study was to uncover the nature and value associated with involvement in "Modern Band" (rock band), the primary, not supplemental, means to music education in one US school. The values that emerged—music, community, identity, teacher, and classroom management—overlap considerably with the benefits and values identified by adolescents in traditional concert band, orchestra, and choir. These results provide data worthy of consideration as readers ponder the viability of rock band as a medium of school-based music education and a way to connect meaningfully with more secondary-school students. Evidence suggests that if there are reasons to reject the rock band, the source for the skepticism should not be the values accrued and identified by its participants. This case is an example of meaningful, authentic, and valuable music education that is positioned between the extremes of formal and informal learning, process and product orientation, and teacher- and student-centered pedagogy.